Status społeczny matek dzieci pozamałżeńskich w Polsce przełomu XX i XXI wieku - Szukalski, Piotr (Wydawnictwo Naukowe UAM, 2008)
The last two decades were a period of increase in numbers and proportion of out-ofwedlock births in Poland. It raised a question if the increase is related with changes in socio-economic status of mothers of the extramarital children. Data on the status of the mothers from the last decades were compared. Generally, independently on the period unmarried mothers had worse status defined in terms of age, educational attainment, and main source of maintenance. The analyzed data suggested further increase in proportion of extramarital births due to generational effect.
Social status of unmarried mothers in Poland at the turn of the 20lh and 21st century